The Influence of Learning Interest and Independence on Student’ Learning Achievement in Social Sciences Subject at SDN 33 Boddie - Hilda Sakti Anwar; Hidayah Quraisy; Sulfasyah Sulfasyah (Edumaspul: Jurnal Pendidikan, 2022)
This study aimed to determine the influence of interest and independence in learning on students' learning achievement in social studies topic of class V SDN 33 Boddie. This research was quantitative. This study involved a sample of 25 students in class V. This data analysis technique deployed a questionnaire or a closed questionnaire, which the researcher made to the respondents. Furthermore, the data was analyzed using SPSS v.22 by looking for the description results, regression analysis requirements test, linearity test, multicollinearity test, and hypothesis test.The study results were based on hypothesis testing where the value of Sig was.0.015 <0.05 and the T-count was2.467> 2.064. And there was an effect of learning independence on learning achievement, which can be seen in the hypothesis test 0.015 < 0.05, and the T-count value was 3.568 > 2.064. This study found the results were very influential on students' learning interests on learning achievement because, with the student's interests, their learning achievement increased as well. Students with a high level of independence had a better chance of achieving better learning. On the other hand, students with a low level of independence got a smaller chance of achieving learning achievement. The higher the independence of students, the higher their learning achievement.